Antioxidant Agriculture for Stress-Resilient Crop Production: Field Practice - Yao Sun; Xianzhi Xie; Chang-Jie Jiang (MDPI AG, 2024)
Oxidative stress, resulting from the excessive production of reactive oxygen species, is a common and major cause of cellular damage in plants exposed to various abiotic stresses. To address this challenge, we introduce the concept of antioxidant agriculture as a comprehensive strategy to improve stress tolerance and thus crop productivity by minimizing oxidative stress levels in the field environment. This strategy encompasses a diverse range of approaches, including genetic engineering, the exogenous application of antioxidant agents, microbial inoculation, and agronomic practices, to reinforce the plant's intrinsic antioxidant defense system and mitigate oxidative stress. We present recent successful studies of antioxidant measures that have been validated in field conditions, along with our perspective on achieving antioxidant agriculture.